2021
DOI: 10.3390/agronomy11091852
|View full text |Cite
|
Sign up to set email alerts
|

New Pathotype Nomenclature for Better Characterisation the Virulence and Diversity of Blumeria graminis f.sp. avenae Populations

Abstract: Fungal cereal pathogens, including Blumeria graminis f.sp. avenae, have the ability to adapt to specific conditions, which in turn leads to overcoming host resistance. An important aspect is the standardized way of characterizing the races and pathotypes of the pathogen. In the presented work, for the first time it was proposed to use a unified letter code that allows describing the pathotypes of B. graminis f.sp. avenae. The set of 14 oat genotypes were used as a differential set. This set included genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Avenae isolates collected from different parts of Europe. These differences suggested that the effectiveness of resistance genes varied from region to region, e.g., for many years, the Pm3 gene was considered ineffective in Poland [ 18 , 19 , 20 ] but in the current study its high resistance against isolates from Ireland and Finland was demonstrated. This research also showed that the virulence level of the population collected in Poland was very similar to that identified in previous years [ 18 , 19 ], indicating that changes in the pathogen population were slow.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Avenae isolates collected from different parts of Europe. These differences suggested that the effectiveness of resistance genes varied from region to region, e.g., for many years, the Pm3 gene was considered ineffective in Poland [ 18 , 19 , 20 ] but in the current study its high resistance against isolates from Ireland and Finland was demonstrated. This research also showed that the virulence level of the population collected in Poland was very similar to that identified in previous years [ 18 , 19 ], indicating that changes in the pathogen population were slow.…”
Section: Discussionmentioning
confidence: 69%
“…Based on binary matrix, the analysed B. graminis f. sp. avenae isolates were classified into appropriate pathotypes according to the methodology described by Okoń et al [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okoń et al [ 17 ] and Cieplak et al [ 33 ] showed that the resistance of the Pm12 gene is maintained at a level that allows for a satisfactory protection of plants against B. graminis f. sp. avenae .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the isolates differed in the level of virulence in relation to the described powdery mildew resistance genes. According to the nomenclature proposed by Okoń et al [ 17 ], the CZE isolate was classified as pathotype TBBB, which means that it was virulent to Pm1 , Pm3 , Pm6 and Pm3+8 genes. The CHR isolate was virulent to Pm1 , Pm3 , Pm6 , Pm3+8 , Pm9 and Pm11 and represented pathotype TBHB.…”
Section: Methodsmentioning
confidence: 99%